Humanistic Values-Based Islamic Education as a Preventive Measure Against Juvenile Delinquency at SMP Ma’arif NU 3 Purwokerto - Destin Dwi Pangesti; Muh. Hanif (Jurnal Evaluasi dan Pembelajaran, 2026)
The phenomenon of juvenile delinquency in junior high school environments is an increasingly complex educational issue that requires a sustainable preventive approach. Social changes, the influence of peer groups, and the development of information technology—which are not always balanced by the reinforcement of moral values and character—are factors driving the emergence of various forms of deviant behavior among students. These conditions demand that education, particularly Islamic Religious Education (IRE), focus not only on cognitive development but also on shaping students’ attitudes, character, and humanistic values. This article aims to analyze humanistic-value-based PAI instruction as a preventive measure to curb juvenile delinquency at SMP Ma’arif NU 3 Purwokerto. This study employs a qualitative approach using a case study method conducted at SMP Ma’arif NU 3 Purwokerto. The research subjects consisted of one PAI teacher, one guidance counselor, and seven eighth- and ninth-grade students selected through purposive sampling. Data collection was conducted through observation, in-depth interviews, and documentation, while data analysis was carried out through the stages of data reduction, data presentation, and systematic conclusion drawing. The research results revealed three main findings. First, the implementation of humanistic-based PAI learning is realized through a dialogic learning process, teacher role modeling, and respect for the dignity, potential, and diversity of students in teaching and learning activities. Second, the internalization of humanistic values in PAI learning fosters behavioral changes in students, characterized by increased empathy, mutual respect, discipline, responsibility, and self-control in school life. Third, humanistic-value-based Islamic Religious Education (IRE) serves as a preventive measure against juvenile delinquency by fostering a school environment that is religious, inclusive, and conducive to the students’ continuous moral development